Revision Anterior Cruciate Ligament Reconstruction Using Bone Dowels - Anthony J. Ignozzi BS; Ian MacLean MD; Mark Miller MD (SAGE Publishing, 2022)
Background: Revision anterior cruciate ligament (ACL) reconstruction is technically challenging and may require the use of bone dowels in either 1 or 2 stages. Indications: The indications for bone dowels include tibial or femoral tunnel malposition or widening of the tunnels. In the patient case, the tibial tunnel aperture was positioned far medial to the native ACL insertion with a horizontal tunnel trajectory and the femoral tunnel was vertical. In addition, there was tunnel widening to 12 mm of both tibial and femoral tunnels. Technique Description: A bone-patellar tendon-bone autograft was harvested and diagnostic arthroscopy was performed. The previous tibial tunnel was sequentially reamed from 8 to 12 mm to adequately overdrill the previous widened tunnel. Next, the femoral tunnel was reamed to 12 mm in similar fashion. Using a tamp and guide pin, a 12 × 30-mm allograft bone dowel was then malleted into the femoral tunnel until it was flush with the medial aspect of the lateral femoral condyle. Another 12 × 30-mm bone dowel was then advanced into the tibial tunnel until it was just below the native articular margin. With the bone dowels securely in place, the ACL reconstruction using the harvested bone-patellar tendon-bone autograft was performed. Results: Werner et al reported a study of 12 patients who had excellent incorporation of femoral tunnel allograft bone dowels and comparable objective and subjective scoring to 2-stage techniques. Dragoo et al reported a study of 18 patients with tibial tunnel allograft bone dowels that demonstrated significant increases in patient-reported outcome measures and a significant decrease in tunnel widening. Discussion/Conclusion: Revision ACL reconstruction may require bone dowels if there are malpositioned tunnels or if there is tunnel widening. Overall, the literature demonstrates that 1-stage revision outcomes have been comparable to reported 2-stage revision outcomes, both of which are satisfactory.